Relationship Between Proactive Personality and Job Performance of Chinese Nurses: The Mediating Role of Competency and Work Engagement - Hu, Xuehui; Zhao, Rong; Gao, Jing; Li, Jianzhen; Yan, Pei; Yan, Xiaofei; Shao, Shuai; Su, Jingkuan; Li, Xiaokang (Frontiers in Psychology, 2021)
Background: As one of the main participants in health care, nurses is esteemed an important driving force for the vigorous health care development. Studies report that nurses’ proactive personality has positive effects on their job performance, however, this relationship acquires further understanding. Objective: A cross-section study was performed to explore the relationship between nurses’ proactive personality and job performance, the mediating role of nurses’ competency and work engagement in this relationship was also evaluated. Methods: The study was performed in a large third-degree general hospital in October, 2019, Xi’an, PR China. A sample of 246 nurses participated in this cross-sectional study. Proactive personality was assessed with the Proactive Personality Questionnaire (PPS), job performance was assessed by Heilman three-item measurements, nurse competence was estimated with Nurse Competency Scale (NCS), and work engagement was assessed with the Utrecht Work Engagement Scale (UWES). The structural equation model was used to test the main hypotheses. Results: The structural equation model analysis revealed that work engagement partially mediated the association between proactive personality and job performance. The serial two-mediator model which was used to explore the association between proactive personality and job performance through competency and work engagement, in sequence, was demonstrated. Conclusion: This study demonstrates that work engagement partially mediated the association between nurses’ proactive personality and their job performance. The serial two-mediator model demonstrated that proactive personality was associated with job performance via competency and work engagement. This study also revealed the critical role of nursing managers in understanding the nurses’ proactive personality, which would facilitate them to enhance the latter’s competency and promote their work engagement. All these will in turn constantly improve the overall quality of nursing and advance professional development of nursing and benefits for patients.